Kecenderungan Berita Kongres Luar Biasa (KLB) PSSI di Media Indosport.com - Ruslan Ramli; Fildzah Yumna Fasya (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2021)
This research discusses the news of the PSSI Extraordinary Congress (KLB) published by indosport.com in November 2019. This event will elect the PSSI Chairperson for the 2019-2024 period. This study aims to determine the trend of indosport.com news issues towards PSSI outbreaks by using content analysis techniques with descriptive quantitative methods. The results of this study indicate that the struggle for the Chairperson of the PSSI is the most prominent issue as news. Regarding the issue of seizing the chair for chairperson, the direction of indosport.com news tends to be negative. Overall, however, the majority of the coverage was neutral. In terms of news types, soft news is the type of news that appears most often. Meanwhile, in the resource aspect, the candidate for chairperson is the most dominant. Indosport.com also tends to use its journalist coverage rather than taking it from other news agencies. Then the informative side is the most dominant writing style.